2002
DOI: 10.1089/105072502321085153
|View full text |Cite
|
Sign up to set email alerts
|

Combretastatin A4 Phosphate Has Primary Antineoplastic Activity Against Human Anaplastic Thyroid Carcinoma Cell Lines and Xenograft Tumors

Abstract: Anaplastic thyroid carcinoma (ATC) is a fatal malignancy the clinical outcome of which is unaltered by current therapeutic modalities. A recent phase 1 clinical trial of combretastatin A4 phosphate (CA4P) produced a long-lasting total remission in a patient with ATC. CA4P is a tubulin-binding agent derived from the African bush willow, Combretum caffrum, which possesses tumor vascular-targeting activity. In order to discriminate primary antineoplastic effects from tumor antivascular activity, we evaluated CA4P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 23 publications
1
26
0
1
Order By: Relevance
“…However, the t 1/2 of the slow clearance phase in this study was similar to the t 1/2 reported for 131 I-A5B7 in the original single agent phase I study (9). Another consideration is that CA4P, in common with other microtubule-binding agents, has independent direct cytotoxic activity (27)(28)(29) that may be additive or synergistic with radiation in inducing marrow toxicity. In a phase I trial in which CA4P was given 60 minutes after carboplatin, dose-limiting thrombocytopenia was reported for carboplatin AUC 5 mg min/mL with CA4P at a relatively low dose of 36 mg/m 2 (30).…”
Section: Discussionsupporting
confidence: 79%
“…However, the t 1/2 of the slow clearance phase in this study was similar to the t 1/2 reported for 131 I-A5B7 in the original single agent phase I study (9). Another consideration is that CA4P, in common with other microtubule-binding agents, has independent direct cytotoxic activity (27)(28)(29) that may be additive or synergistic with radiation in inducing marrow toxicity. In a phase I trial in which CA4P was given 60 minutes after carboplatin, dose-limiting thrombocytopenia was reported for carboplatin AUC 5 mg min/mL with CA4P at a relatively low dose of 36 mg/m 2 (30).…”
Section: Discussionsupporting
confidence: 79%
“…Combretastatin A4 phosphate (CA4P) is a tubulin-binding agent that inhibits tumor blood flow at doses less than 10% of the maximum tolerated dose (10); its rapid, selective, and extensive inhibition of tumor blood flow makes it a promising novel anticancer drug (11). CA4P has antineoplastic activity against ATC cell lines and xenografts (12). In a phase I trial, CA4P, given iv every 3 wk, induced remission of ATC for 30 months in one patient (13).…”
Section: Discussionmentioning
confidence: 99%
“…Further experimental treatment options being explored include combretastatin A4-phosphate (CA4P) and bone morphogenetic protein (BMP-7). Combretastatin is an effective antitumor vascular targeting agent currently in phase I trials [58,59]. Bone morphogenetic protein (BMP-7) significantly inhibits tumor growth in four of six human ATC cell lines [60].…”
Section: Future Researchmentioning
confidence: 99%